RANCANG BANGUN SISTEM INFORMASI IT HELPDESK DENGAN PRIORITAS KERJA BERBASIS WEB (STUDI KASUS : PT PELABUHAN INDONESIA III CABANG TANJUNG PERAK) - Nugroho, Hendra Setyo A.; Sukmaaji, Anjik; Jatmiko, Kurniawan (Jurnal JSIKA, 2013)
Division of Management & Information Systems (MIS) is a division that has the responsibility to maintain and protect the information and communication technology (ICT) that existed at Tanjung Perak Branch PELINDO III in order to run properly. In dealing with any issues regarding IT tools, SMI division experienced difficulties in accepting the complaint information and perform assignments to address those problems. Obstacles that complicate operations division SMI may cause disruption of the company´s business processes. Of the problems IT Helpdesk information systems made ​​by observing work in priority handling to provide helpdesk solution. Priority of the problem is determined by adopting the method delbeq and supporting information to the management, the system provides information about the value of MTTR, MTBF, reliability and availability of IT devices. From the results of evaluation of the system is done, the system is able to provide reporting facilities issues, advising assignments, provides information on the issues, provide information MTTR, MTBF, availability and reliability. Keyword: helpdesk, availability, reliability